2020
DOI: 10.1002/lt.25732
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Infection in the United States: Current Understanding of the Prevalence and Significance in the Liver Transplant Patient Population and Proposed Diagnostic and Treatment Strategies

Abstract: Hepatitis E virus (HEV), of the family Herpesviridae, is a virus that infects nearly 20 million people per year throughout the world. HEV is most commonly transmitted via the fecal-oral route and has long been described as a virus that afflicts only those in resource-poor countries. However, HEV has been detected in numerous animal carriers, various food sources, and even in human blood products in resource-rich regions of the world. HEV is of importance in the transplant patient population because of its abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…[15][16][17][18][19][20] It is also puzzling to note, that, despite genotype 3 HEV widely circulating in North America where many high-volume transplant centres are located, chronic hepatitis E has rarely been reported in this region. 21 For example, in a cohort of 145 liver transplant recipients from the United States, patients were found to be at risk of acquiring HEV, but no chronic cases were observed. 22 One particular concern is the fact that a widely accessible commercial assay is not available for HEV diagnosis in North America, and thus the true burden of HEV infection may be underestimated in this region.…”
Section: Epidemiology In Immunocompromised Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20] It is also puzzling to note, that, despite genotype 3 HEV widely circulating in North America where many high-volume transplant centres are located, chronic hepatitis E has rarely been reported in this region. 21 For example, in a cohort of 145 liver transplant recipients from the United States, patients were found to be at risk of acquiring HEV, but no chronic cases were observed. 22 One particular concern is the fact that a widely accessible commercial assay is not available for HEV diagnosis in North America, and thus the true burden of HEV infection may be underestimated in this region.…”
Section: Epidemiology In Immunocompromised Populationsmentioning
confidence: 99%
“…22 One particular concern is the fact that a widely accessible commercial assay is not available for HEV diagnosis in North America, and thus the true burden of HEV infection may be underestimated in this region. 21 Very recently, data on 2 patients with COVID-19 who were infected with genotype 3 HEV were reported in the United Kingdom. One case further progressed to chronic infection, which is likely to have been associated with prolonged lymphopenia and treatment with immunosuppressive medications including tocilizumab and steroids.…”
Section: Epidemiology In Immunocompromised Populationsmentioning
confidence: 99%
“…12 In addition to liver damage, acute and chronic HEV infections can cause neurological impairments, renal impairment, and gastrointestinal diseases. 13 To date, various studies of HEV infection in SOT recipients have been reported in European and American countries but not yet in China. Although several investigations about the prevalence and clinical courses of HEV infection in SOT recipients were performed, few studies provide data on de novo HEV infection and accumulated de novo HEV infection rate after transplantation with long-term followup.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis E is a disease caused by hepatitis E virus (HEV) (1). HEV is a widespread pathogen found in wild animals (boar, deer) (2,3), domestic pigs (4,5), rats (6,7), chickens (8,9), and humans (10,11). The disease in humans is mostly defined as self-limiting but can be lethal in people with underlying health conditions (12,13), immunosuppressed (14,15), and during pregnancy (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%